Factors affecting interest in utilization and use of online shop (study on shopee customers) - Hidayah, Sayidah Rohmatul; Chyntia Eka Putri (SHM Publisher, 2021)
The development of information technology has led to the emergence of various e-commerce services. One of them is engaged in the mobile marketplace, namely Shopee. Shopee as a mobile marketplace is always faced with competitors. Therefore, this study aims to determine the factors that influence the interest in the use and use of the online shop, especially the Shopee application. In this study, the UTAUT2 framework was used, where this framework is a framework that is often used to determine user intentions and behavior in using technology or applications. The UTAUT2 framework has seven main constructs and in this study one construct is added, namely trust. The results of this study indicate that the UTAUT2 framework with additional trust constructs has a positive regression weight for all UTAUT2 constructs and additional trust constructs except for the effort expectancy and hedonic motivation constructs. This shows that all UTAUT2 constructs and additional trust constructs have a positive effect on the intention to use the Shopee application when shopping online except for the effort expectancy and hedonic motivation constructs. Intention to use also has a positive effect on user behavior to use the Shopee application when shopping online.